UNMANNED AERIAL VEHICLES FOR GEOLOGICAL APPLICATIONS - Nikolakopoulos, K.G.; Koukouvelas, I.; Argyropoulos, N.G. (Bulletin of the Geological Society of Greece, 2016)
Remote Sensing and photogrammetric techniques have always been used in geological applications. Current advancements in the technology behind Unmanned Aerial Vehicles (UAVs), in accordance with the consecutive increase in affordability of such devices and the availability of photogrammetric software, makes their use for large or small scale land mapping more and more popular. With the UAVs being used for mapping, the problems of increased costs, time consumption and the possible accessibility problems -due to steep terrain-, are all solved at once. In this study, a custom-made UAV with 2 cameras onboard, is used to monitor two complex –regarding their topography- regions in Western Greece. One open pit limestone mine and a landslide occurring on sandy-clayous sediments. Both regions were mapped using surveying instruments like tachymeters and geodetic GPS, as well as using the aforementioned UAV system. 3D models of both regions were created using off-the-shelf photogrammetric software. For the creation of the 3D models, multiple targets were placed on the ground, to indicate GCPs with precisely known coordinates that could be identified in the high-resolution air photos, in order to maintain low Root Mean Square Error, while creating the DSMs and Orthophotos. In addition, the fish-eye effect caused by the cameras’ wide-angle lens was taken into consideration, regarding whether or not it affects the models’ overall geometric accuracy. Finally, the 3D models were compared to the survey measurements and the results are presented in this paper.